A conserved proline residue in Dothideomycete Avr4 effector proteins is required to trigger a Cf‐4‐dependent hypersensitive response. (7th May 2015) - Mesarich, Carl H.; Stergiopoulos, Ioannis; Beenen, Henriek G.; Cordovez, Viviane; Guo, Yanan; Karimi Jashni, Mansoor; Bradshaw, Rosie E.; de Wit, Pierre J. G. M.
Summary: CfAvr4, a chitin‐binding effector protein produced by the Dothideomycete tomato pathogen Cladosporium fulvum, protects the cell wall of this fungus against hydrolysis by secreted host chitinases during infection. However, in the presence of the Cf‐4 immune receptor of tomato, CfAvr4 triggers a hypersensitive response (HR), which renders the pathogen avirulent. Recently, several orthologues of CfAvr4 have been identified from phylogenetically closely related species of Dothideomycete fungi. Of these, DsAvr4 from Dothistroma septosporum also triggers a Cf‐4‐dependent HR, but CaAvr4 and CbAvr4 from Cercospora apii and Cercospora beticola, respectively, do not. All, however, bind chitin. To identify the region(s) and specific amino acid residue(s) of CfAvr4 and DsAvr4 required to trigger a Cf‐4‐dependent HR, chimeric and mutant proteins, in which specific protein regions or single amino acid residues, respectively, were exchanged between CfAvr4 and CaAvr4 or DsAvr4 and CbAvr4, were tested for their ability to trigger an HR in Nicotiana benthamiana plants transgenic for the Cf‐4 immune receptor gene. Based on this approach, a single region common to CfAvr4 and DsAvr4 was determined to carry a conserved proline residue necessary for the elicitation of this HR. In support of this result, a Cf‐4‐dependent HR was triggered by mutant CaAvr4 and CbAvr4 proteins carrying an arginine‐to‐proline substitution at this position. This study provides the first step in deciphering how Avr4 orthologues from different Dothideomycete fungi trigger a Cf‐4‐dependent HR.